2021
DOI: 10.3389/fvets.2021.667175
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Antimicrobial Resistance of Ruminant Mycoplasmas Using a Clinical Surveillance Network

Abstract: Antimicrobial resistance (AMR) surveillance of mycoplasmas of veterinary importance has been held back for years due to lack of harmonized methods for antimicrobial susceptibility testing (AST) and interpretative criteria, resulting in a crucial shortage of data. To address AMR in ruminant mycoplasmas, we mobilized a long-established clinical surveillance network called “Vigimyc.” Here we describe our surveillance strategy and detail the results obtained during a 2-year monitoring period. We also assess how fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
(106 reference statements)
5
9
0
Order By: Relevance
“…Our observations suggest that the efflux system in mycoplasma allows tetracycline resistance up to 4 µg/mL and might facilitate the acquisition of a target mutation for higher resistance. This is consistent with the fact that the M. putrefaciens species, which has remained so far mostly susceptible to tetracycline [ 6 ], exhibits no or a weak efflux. On the experimental basis proposed here, it would be interesting to further test the contribution of efflux in other Mycoplasma species with high tetracycline MICs and the corresponding mutations in the target genes, such as M. bovis .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our observations suggest that the efflux system in mycoplasma allows tetracycline resistance up to 4 µg/mL and might facilitate the acquisition of a target mutation for higher resistance. This is consistent with the fact that the M. putrefaciens species, which has remained so far mostly susceptible to tetracycline [ 6 ], exhibits no or a weak efflux. On the experimental basis proposed here, it would be interesting to further test the contribution of efflux in other Mycoplasma species with high tetracycline MICs and the corresponding mutations in the target genes, such as M. bovis .…”
Section: Discussionsupporting
confidence: 86%
“…In a previous study, we observed a moderate decrease in susceptibility to oxytetracycline in some Mycoplasma strains belonging to species involved in contagious agalactia syndrome of small ruminants, M. agalactiae , Mmc and Mcc [ 10 ]. Only Mput did not show any in vitro increased tetracycline MICs, which was recently confirmed [ 6 ]. Three main mechanisms, namely target protection, target modification, and efflux extrusion, are known to result in tetracycline resistance in bacteria.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the meanwhile, epidemiological cut-off values (ECOFFs), i.e., the highest MIC that defines the upper end of the wild-type (WT) MIC distribution, could be used as surrogates, i.e., thresholds for early warning of acquired phenotypic resistance, but not for guiding therapy, as non-WT isolates are not always clinically resistant. Furthermore, the process of setting ECOFFs is also challenging, as, according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST, https://www.eucast.org, accessed on 1 September 2021) standard operating procedures, it requires aggregation of MIC data obtained in different laboratories using standardized AST methods [98]. Today, if more and more results are regularly published, they are hardly comparable, even when comparing MIC data, as there might be an influence of the method [27].…”
Section: Susceptibility Testing and Epidemiology Of Resistancementioning
confidence: 99%